Mild Traumatic Brain Injury-Induced Disruption of the Blood-Brain Barrier Triggers an Atypical Neuronal Response - Munoz-Ballester, Carmen; Mahmutovic, Dzenis; Rafiqzad, Yusuf; Korot, Alia; Robel, Stefanie (Frontiers in Cellular Neuroscience, 2022)
Concussive TBI (cTBIMildTBI (mTBI), which affects 75% of TBI survivors or more than 50 million people worldwide each year, can lead to severe consequences including sleep disturbances, cognitive impairment, mood swings, and post-traumatic epilepsy. in a subset of patients. To interrupt the progression of these comorbidities, identifying early pathological events is key. Recent studies have shown that microbleeds, caused by mechanical impact, persist for months after cTBImTBI and are correlated to worse cTBImTBI outcomes. However, the impact of cTBImTBI-induced blood-brain barrier damage on neurons is yet to be revealed. We used a well-characterized mouse model of cTBImTBI that presents with frequent and widespread but size-restricted damage to the blood-brain barrier to assess how neurons respond to exposure of blood-borne factors in this pathological context. We used immunohistochemistry and histology to assess the expression of neuronal proteins in excitatory and inhibitory neurons after cTBImTBI. We observed that the expression of NeuN, Parvalbumin, and CamKII was lost within minutes in areas with blood-brain barrier disruption. Yet, the neurons remained alive and could be detected using a fluorescent Nissl staining even six months later. A similar phenotype was observed after exposure of neurons to blood-borne factors due to endothelial cell ablation in the absence of a mechanical impact, suggesting that entrance of blood-borne factors into the brain is sufficient to induce the neuronal atypical response. Changes in postsynaptic synaptic spines were observed indicative of functional changes. Thus, this study demonstrates that exposure of neurons to blood-borne factors causes a rapid and sustained loss of neuronal proteins and changes in spine morphology in the absence of neurodegeneration, a finding that is likely relevant to many neuropathologies.